Zinc toxicosis in a cat associated with ingestion of a metal screw nut. Issue 2 (November 2022) - Yu, Jane; Jenkins, Elizabeth; Podadera, Juan M; Proschogo, Nicholas; Chan, Ringo; Boland, Lara
Case summary: A 3-year-old female neutered domestic shorthair cat was presented for vomiting, inappetence and weight loss. The cat developed moderately regenerative anaemia, moderately increased alanine transaminase and alkaline phosphatase activities, hyperbilirubinaemia and prolonged activated partial thromboplastin time. Abdominal ultrasound identified gastric wall thickening and changes suggestive of pancreatitis. Gastroduodenoscopy identified a metal screw nut in the pylorus, which was removed with rat tooth forceps. Metal analysis and serum zinc concentration using leftover serum collected at admission were performed after screw nut removal. Serum zinc concentration was markedly elevated, confirming a diagnosis of zinc toxicosis. Metal analysis of the screw nut showed that the major metal component was zinc. The cat recovered after screw nut removal and supportive care. Clinical signs resolved and the serum zinc concentration reduced significantly after screw nut removal. Relevance and novel information: Reports of zinc toxicosis in cats are scarce, possibly due to the more discriminating eating habits of this species. To our knowledge, this is the first report of zinc toxicosis causing haemolytic anaemia, liver enzyme activity increases, gastrointestinal signs and pancreatitis in a cat associated with ingestion of a zinc-containing metal object.